Uvaria huana (Annonaceae), a replacement name for an Asian species - Wang, Ruijiang (Phytotaxa, 2014)
Uvaria huana is proposed as a new name for U. yunnanensis (Hu) L. L. Zhou, Y. C. F. Su & R. M. K. Saunders (2009), a later homonym of U. yunanensis Li (1978).